Strategi Peningkatan Kapabilitas Perumahan Desa Klangonan untuk Memperbaiki Kualitas Hidup, melalui Pemanfaatan Potensi Home Based Enterprises - Firdha Ayu Atika; Esty Poedjioetami (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
Housing Capabilities and Home-Based Enterprises (HBE) were concept, that support the success of sustainable housing development.  This research aims to improve the quality of life of the Klangonan Village inhabitant, through the existence of HBE potential. The research methods used were mixed methods, combining qualitative data and quantitative data.  This study used qualitative SWOT analysis techniques, which begin by determining internal factors and external factors.  The results of this study showed that HBE development was very necessary, by doing the construction of housing and residential infrastructure. In addition, the relationship of the kinship system between citizens could also be used to develop business cooperation activities.